2011
DOI: 10.1371/journal.pone.0023278
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic-Derived Polyphosphate Enhances the Epithelial Barrier Function and Maintains Intestinal Homeostasis through Integrin–p38 MAPK Pathway

Abstract: Probiotics exhibit beneficial effects on human health, particularly in the maintenance of intestinal homeostasis in a complex manner notwithstanding the diversity of an intestinal flora between individuals. Thus, it is highly probable that some common molecules secreted by probiotic and/or commensal bacteria contribute to the maintenance of intestinal homeostasis and protect the intestinal epithelium from injurious stimuli. To address this question, we aimed to isolate the cytoprotective compound from a lactob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 41 publications
4
152
0
1
Order By: Relevance
“…The grade of inflammation in the mice administered poly P was significantly lower than that in the mice administered PBS (p<0.01) (Figures 6A-D). The immunohistochemical reactivity for the anti-collagen IV antibody was 22 increased in the colons of mice with TNBS-induced colitis compared to the control mice, and that in the mice treated with poly P was repressed to a similar level as was observed in the control mice. The intensities of fluorescence in the colons of the poly P-administered mice were significantly lower than those observed in the PBS-administered mice (p<0.05) ( Figures 6E-H).…”
Section: Tnbs-induced Colitismentioning
confidence: 64%
See 1 more Smart Citation
“…The grade of inflammation in the mice administered poly P was significantly lower than that in the mice administered PBS (p<0.01) (Figures 6A-D). The immunohistochemical reactivity for the anti-collagen IV antibody was 22 increased in the colons of mice with TNBS-induced colitis compared to the control mice, and that in the mice treated with poly P was repressed to a similar level as was observed in the control mice. The intensities of fluorescence in the colons of the poly P-administered mice were significantly lower than those observed in the PBS-administered mice (p<0.05) ( Figures 6E-H).…”
Section: Tnbs-induced Colitismentioning
confidence: 64%
“…Thereafter, we chemically synthesized poly P using a poly P-synthesizing enzyme polyphosphate kinase, and found that the synthesized poly P could maintain the intestinal barrier functions via a mechanism involving the intestinal integrin β1-p38 MAPK pathway 22 . Yan F et al also identified two bioactive molecules, p40 and p75, produced by Lactobacillus rhamnosus GG 23 and reported the effects of p40 in protecting the intestinal epithelia from injury and inflammation in an oxazolone-induced colitis model 24 .…”
mentioning
confidence: 99%
“…For example, Polyphosphate (poly-P) is produced by probiotics and it is a bioactive molecule that induced cytoprotective heat shock protein through activation of the integrin-p38 mitogen-activated protein kinase pathway, and it prevents oxidant-induced intestinal barrier weakening. Furthermore, poly-P ameliorated epithelial injury (Segawa et al, 2011). It has been reported that multi-microbe probiotic product VSL#3 normalized monolayer permeability and conductance in stimulated tissues, thus strengthened barrier integrity (Madsen et al, 2001).…”
Section: Mucus Secretionmentioning
confidence: 95%
“…These kinases are a chain of proteins in the cell that communicates signals from a receptor on the surface of the cell to the DNA in the nucleus of the cell. Previous studies have reported that probiotics maintained homeostasis through enhanced MAPK activities (Segawa et al, 2011;Iyer et al, 2008). Increasing activity of MAPKs and their involvement in the regulation of inflammation make them potential targets for novel anti-inflammatory therapeutics.…”
Section: Discussionmentioning
confidence: 99%